Comparative Genomics of Transcriptional Control in the Human Malaria Parasite Plasmodium falciparum - Coulson, Richard M.R.; Hall, Neil; Ouzounis, Christos A. (Genome Research, 2004)
The life cycle of the parasite Plasmodium falciparum, responsible for the most deadly form of human malaria, requires specialized protein expression for survival in the mammalian host and insect vector. To identify components of processes controlling gene expression during its life cycle, the malarial genome—along with seven crown eukaryote group genomes—was queried with a reference set of transcription-associated proteins (TAPs). Following clustering on the basis of sequence similarity of the TAPs with their homologs, and together with hidden Markov model profile searches, 156 P. falciparum TAPs were identified. This represents about a third of the number of TAPs usually found in the genome of a free-living eukaryote. Furthermore, the P. falciparum genome appears to contain a low number of sequences, which are highly conserved and abundant within the kingdoms of free-living eukaryotes, that contribute to gene-specific transcriptional regulation. However, in comparison with these other eukaryotic genomes, the CCCH-type zinc finger (common in proteins modulating mRNA decay and translation rates) was found to be the most abundant in the P. falciparum genome. This observation, together with the paucity of malarial transcriptional regulators identified, suggests Plasmodium protein levels are primarily determined by posttranscriptional mechanisms.
10.1101/gr.2218604